Música & matemática: uma proposta pedagógica para os anos inicias - GOMES, Manoel Jordan Menezes (2023)
This dissertation works on the relationship between mathematics and music and its applications in the classroom, focusing mainly on enriching the knowledge of musicians and mathematicians and demonstrating these relationships in practice within the classroom, the dissertation consists of several themes that will assist this study in a way the makes knowledge richer and much more attractive by developing the study of fractions, volume measurements, proportionality and works with the musical base showing the development of music and mathematics from the studies of Pythagoras showing the evolution to the present day, showing teaching tactics in classroom teaching that shows in practice how mathematics is music contributes to students’ learning, enriching didactics and making learning more meanningful and attractive.